Advantages of Using the "Mental Attack" Teaching Method in the Educational Process or the Method of "Hitting Ten Rabbits with One Bullet" - Sh. Davletova; N. R. Toychiyeva (International Journal on Integrated Education, 2022)
This article presents the results of improving the quality of lessons using the "Brainstorming" teaching method in the educational system. First of all, general information, advantages and disadvantages of this method were studied. It was mentioned that due to the active participation of the students in learning the process, the subject remains in their memories for a long time and forms an active knowledge reserve.